2019
DOI: 10.1007/s13593-019-0594-y
|View full text |Cite
|
Sign up to set email alerts
|

Codesigning biodiversity-based agrosystems promotes alternatives to mycorrhizal inoculants

Abstract: Facing the challenge of the ecological transition of agriculture, biodiversity opens new avenues to enhance ecological interactions and reduce chemical input dependency. Designing biodiversity-based agrosystems requires an agroecological approach that combines key principles: exploring a wide range of concepts and solutions, adopting systemic reasoning, implementing a sitespecific approach, developing an action-oriented process, and maintaining a continuous improvement dynamic. This type of approach has never … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In undisturbed soil, i.e., no-till cropping, cover crops or crop rotation could benefit succeeding main crops by supplying AMF communities [47,52,53]. Thus, designing a mycorrhizafriendly cropping system using a diverse rotational sequence, utilizing cover crops, and adopting no-till agriculture [57] and an agroecological approach, such as a donor crop, where the donor crop is intercropped with the target crop, could help harness the functional diversity of indigenous AMF communities [58]. Moreover, inoculation via donor crop is a more convenient and effective inoculation approach in large-field or woody crops where inoculation could be labor intensive or technically difficult [36].…”
Section: Adopting Practices That Promote the Richness And Diversity O...mentioning
confidence: 99%
“…In undisturbed soil, i.e., no-till cropping, cover crops or crop rotation could benefit succeeding main crops by supplying AMF communities [47,52,53]. Thus, designing a mycorrhizafriendly cropping system using a diverse rotational sequence, utilizing cover crops, and adopting no-till agriculture [57] and an agroecological approach, such as a donor crop, where the donor crop is intercropped with the target crop, could help harness the functional diversity of indigenous AMF communities [58]. Moreover, inoculation via donor crop is a more convenient and effective inoculation approach in large-field or woody crops where inoculation could be labor intensive or technically difficult [36].…”
Section: Adopting Practices That Promote the Richness And Diversity O...mentioning
confidence: 99%
“…Although conventional agricultural management can exert adverse effects on AM fungal communities ( Helgason et al, 1998; Oehl et al, 2003), a high diversity of AMF can still be found in agricultural fields ( Hijri et al., 2006; Sasvári and Posta , 2010). Thus, the use of the native AMF community to enhance mycorrhizal benefit for crops might be an alternative to the inoculation of non‐native mycorrhizal strains ( Chave et al, 2019). However, a better understanding of the effects of the native AMF community on the performance of the various crop species and crop varieties under field conditions is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Although conventional agricultural management can exert adverse effects on AM fungal communities (Helgason et al 1998;Oehl et al 2003), high diversity of AMF can still be found in agricultural fields (Hijri et al 2006;Sasvari et al 2011). Thus, using the native AMF community to enhance mycorrhizal benefit for crops could be an alternative besides inoculating non-native mycorrhizal strains (Chave et al 2019). But it is a prerequisite to understand how the native AMF community affects the performance of different crop species and varieties under field conditions.…”
Section: Introductionmentioning
confidence: 99%